Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1017/s1049023x18000365
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Prehospital Analgesia with Fascia Iliaca Compartment Block for Femoral Bone Fractures: A Systematic Review

Abstract: The FICB is suitable for use in the prehospital environment for the management of femoral fractures. It has few adverse effects and can be performed with a high success rate by practitioners of any background. Studies suggest that FICB is a useful analgesic technique, although further research is required to investigate its effectiveness compared to systemic opioids. HardsM, BrewerA, BessantG, LahiriS. Efficacy of prehospital analgesia with Fascia Iliaca Compartment Block for femoral bone fractures: a systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Although the studies on FNB are few and small, there are more data on FICB in the pre‐hospital setting as outlined in a recent review 10 . The target in FICB is more lateral to the neurovascular bundle than in FNB and performing the block does not require special equipment, which may contribute to its popularity in the pre‐hospital setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the studies on FNB are few and small, there are more data on FICB in the pre‐hospital setting as outlined in a recent review 10 . The target in FICB is more lateral to the neurovascular bundle than in FNB and performing the block does not require special equipment, which may contribute to its popularity in the pre‐hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review on fascia iliaca compartment blocks (FICBs) concluded that this technique is suitable for pre‐hospital management of pain from femoral fractures. Only minor side effects were reported and FICB can be administered by providers with varying backgrounds 10 . The FNB maybe a more familiar technique than FICB for most anaesthesiologists, but to our knowledge no systematic review has been published on the use of FNB in the pre‐hospital setting.…”
Section: Introductionmentioning
confidence: 99%
“…Fascia iliaca compartment block is used to block these nerves to meet the needs of lower limb analgesia and anesthesia. It is used for anesthesia and analgesia of the hip, knee and thigh[15,16]. Ultrasound-guided fascia iliaca compartment block can be divided into parallel puncture of the inguinal ligament, and improved vertical puncture of the inguinal ligament.…”
Section: Discussionmentioning
confidence: 99%
“…16 Evans, et al 2 reported prehospital administration of FICB for patients with suspected fractures at the scene of trauma, using the landmark technique with good results. Hards, et al 17 in their systematic review concluded that FICB is appropriate technique for prehospital pain management, with a high success rate and few adverse effects. It was concluded that it is easily learned and effective procedure for preoperative pain.…”
Section: Dexmedetomidinementioning
confidence: 99%